Incorporation of Victim Size in an Examination of Consumer Ethics in South Korea. Issue 2 (May 2014) - Lee, Jungki; Fullerton, Sam
The concept of consumer misbehaviour has become a subject of significant inquiry in recent years. A sample of 239 adults in South Korea provided insight regarding their judgment about the appropriateness of 12 questionable actions undertaken by consumers. The survey used multiple versions that allowed for the manipulation of the scenarios to reflect either a large or a small organisation as the victim of the consumers' actions. The results indicate that South Korean consumers are open to some questionable behaviour, but opposed to others – thus reflecting the situational nature of ethics. The results also document the fact that the size of the victimized organisation is related to the perceived acceptability of the questionable act. The results in this regard were not as predictable as one might expect; however, plausible explanations for this apparent paradox are presented. Managerial implications and future research directions are provided.